Study of multistory tilt-up with varying parameters - Mills, Erin Victoria (Kansas State University, 2021)
Historically, tilt-up concrete construction has been confined to large, single-story warehouses and industrial buildings with a large footprint and few openings. Now, however, given the speed of construction, durability, and economics of tilt-up construction, a demand for selecting tilt-up concrete as a structural system for multistory office, retail, and apartment buildings is on the rise. This report provides an overview of the effect of the construction location, reinforcing steel bar size, reinforcing steel yield strength, number of layers of steel, and number of stories on the design of multistory tilt-up using the slender wall method, when out-of-plane wind loading and gravity loads are applied. An exterior multistory panel is assessed to determine the effect of sundry panel designs for loadbearing walls in multistory tilt-up construction. A two-story, three-story, and four-story panel with a consistent thickness, width, and concrete strength in adjunction to varying reinforcement size, reinforcement strength, layers of reinforcement, and out-of-plane loading is analyzed to determine the impact the design has on the panel. Two-story, three-story, and four-story panels with a floor-to-floor height of 14 feet are used in the parametric study done in this report. All panels have a width of 15 feet and concrete compressive strength of 4,000 psi. The panel thickness is used in conjunction with varying steel reinforcement sizes of a #5 and #6 bar as well as strengths of 60 ksi and 80 ksi. Based on the results found in the parametric study it was concluded that using the alternative method for slender wall analysis is only valid for two- or three-story buildings when normal weight concrete is utilized. It is also apparent that using the same number of bars in a doubly reinforced panel as opposed to a singly reinforced panel resulted in lesser moments and out-of-plane deflections. Further research should be done to analyze how designing multistory tilt-up as a column with varying parameters affects the panel. This study showed that regardless of the applied lateral loads and the amount of reinforcement placed within the panel, the four-story panel design was invalid and should be designed as a column. Increasing the concrete strength may result in a valid panel design and should also be further investigated.
Keywords: Multistory tilt-up with varying parameters